Analysis of acute-phase toxicities of intensity-modulated proton therapy using a model-based approach in pharyngeal cancer patients. (29th December 2020) - Yasuda, Koichi; Minatogawa, Hideki; Dekura, Yasuhiro; Takao, Seishin; Tamura, Masaya; Tsushima, Nayuta; Suzuki, Takayoshi; Kano, Satoshi; Mizumachi, Takatsugu; Mori, Takashi; Nishioka, Kentaro; Shido, Motoyasu; et al.
Abstract: Pharyngeal cancer patients treated with intensity-modulated proton therapy (IMPT) using a model-based approach were retrospectively reviewed, and acute toxicities were analyzed. From June 2016 to March 2019, 15 pharyngeal (7 naso-, 5 oro- and 3 hypo-pharyngeal) cancer patients received IMPT with robust optimization. Simulation plans for IMPT and intensity-modulated X-ray therapy (IMXT) were generated before treatment. We also reviewed 127 pharyngeal cancer patients with IMXT in the same treatment period. In the simulation planning comparison, all of the normal-tissue complication probability values for dysphagia, dysgeusia, tube-feeding dependence and xerostomia were lower for IMPT than for IMXT in the 15 patients. After completing IMPT, 13 patients completed the evaluation, and 12 of these patients had a complete response. The proportions of patients who experienced grade 2 or worse acute toxicities in the IMPT and IMXT cohorts were 21.4 and 56.5% for dysphagia ( P < 0.05), 46.7 and 76.3% for dysgeusia ( P < 0.05), 73.3 and 62.8% for xerostomia ( P = 0.43), 73.3 and 90.6% for mucositis ( P = 0.08) and 66.7 and 76.4% for dermatitis ( P = 0.42), respectively. Multivariate analysis revealed that IMPT was independently associated with a lower rate of grade 2 or worse dysphagia and dysgeusia. After propensity score matching, 12 pairs of IMPT and IMXT patients were selected. Dysphagia was also statistically lower in IMPT than in IMXT ( P < 0.05). IMPT using a model-based approach may have clinical benefits for acute dysphagia.